Growth and Uptake of Sodium and Potassium in Broad Bean (Vicia faba L.) under Salinity Stress - (:unkn) unknown (TAYLOR & FRANCIS INC, 2011)
Vicia faba L. (broad bean or faba bean), a food crop of worldwide importance, is moderately tolerant of saline conditions, such as are increasingly common in Mediterranean countries and in Turkey. Our objective was to determine the influence of two salinity levels [50 and 100 mM sodium chloride (NaCl)] and two potassium salts, potassium nitrate (KNO3) (N1 and N2) or potassium acetate (CH3COOK) (A1 and A2), on the development of seedlings of two cultivars of broad bean (cvs. Eresen 87 and Filiz 99) grown in pots of perlite under controlled greenhouse conditions. Flame photometer (FP) analysis of tissues from roots, stems, and leaves of 3-month-old seedlings showed significant differences in growth, internodal length, and potassium (K+)/sodium (Na+) ratios. The FP analyses revealed that Na+ was the ion most responsible for inhibition of growth parameters seen in both cultivars and salt treatments. K+ contents were consistently higher in cv. Filiz 99 than in cv. Eresen 87. Possible correlations between these data and the tolerance to salinity of these cultivars are discussed.
Keywords: Broad bean; salinity; Vicia faba L; IRRIGATION WATER SALINITY; SALT-STRESS; NACL SALINITY; STOMATAL-RESISTANCE; ION ACCUMULATION; SOIL-SALINITY; PLANTS; TOMATO; CHLORIDE; TOLERANCE